2005
DOI: 10.1057/palgrave.jibs.8400159
|View full text |Cite
|
Sign up to set email alerts
|

A needs-driven approach to expatriate adjustment and career development: a multiple mentoring perspective

Abstract: Although effective in improving socialization, development, and retention in the US domestic context, mentoring would likely benefit expatriates and their firms, but it remains theoretically underdeveloped in the international context. We develop a theory of international mentoring by integrating current perspectives on protean and boundaryless careers with the literature on mentoring and expatriates. Expatriates need multiple mentors to assist their adjustment and development during the pre-departure, expatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
210
0
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(237 citation statements)
references
References 92 publications
9
210
0
10
Order By: Relevance
“…The findings showed the expatriates have difficulties in promotion during assignment abroad. Many employees refuse to accept the international assignment demands because they fear of being left out for promotion Mezias and Scandura [20]. The results are parallel with the previous findings that showed that the element of promotion is the main thing that needs to be considered.…”
Section: Task Satisfactionsupporting
confidence: 83%
“…The findings showed the expatriates have difficulties in promotion during assignment abroad. Many employees refuse to accept the international assignment demands because they fear of being left out for promotion Mezias and Scandura [20]. The results are parallel with the previous findings that showed that the element of promotion is the main thing that needs to be considered.…”
Section: Task Satisfactionsupporting
confidence: 83%
“…While it is obviously difficult for individuals to simply make others like them, there are a number of ways that they can increase the chances that others would like them. For example, expatriates could ensure that they learn about and demonstrate their awareness of relevant social, cultural and business practices (see Mezias & Scandura, 2005) Shay & Baack, 2006), as this could have a significant positive impact on expatriate experience, which has been shown to have a strong relationship their overall job satisfaction (Froese & Peltokorpi, 2011).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For example, if the local practice is to take a short lunch break, and continue to work over the lunch break, an expatriate who is used to taking long lunches that are deemed "work-free zones", would have to adapt and adopt the local practices. Of course, it is the more subtle practices that one could really use help with -for example, if the norm at the new location is that everyone speaks up at meetings, but the real decision This is where HCNs can be extremely useful -first, they can draw upon their own experiences, provide critical information and resources to expatriates (Mezias & Scandura, 2005). Next, HCNs can also help expatriates avoid potential pitfalls by sharing their knowledge and expectations (Caligiuri, 2000).…”
Section: Importance Of Role Information and Social Supportmentioning
confidence: 99%
“…My results show that temporary relocation, even for a few weeks, can have longer-term effects on innovation. This insight also has implications for the broader literature in strategy and international business focused on expatriate movements within multinational firms (Tung, 1998;Mezias and Scandura, 2005). Such intra-firm mobility is often temporary, but the duration of such mobility is often measured in years, not weeks.…”
Section: Contributionsmentioning
confidence: 93%